How private sector remains sustainable during pandemic Covid-19? A case study in Malaysia / Arifha Mohamad ... [et al.] - Mohamad, Arifha; Abd Rahman, Normy Rafida; Ghazali, Kamarull Bahar; Megat Zambri, Wan Anis Aqilah (Universiti Teknologi MARA, Negeri Sembilan, 2021)
The pandemic Covid-19 had been recognized to give a dramatic impact to the health and economic growth of the world. By having an unsecured capital operation to face the challenges, it is hard for the private sectors specially to keep sustained in the industry for the long term. With that, the aim of this study is to identify the impact of motivational factors towards the job sustainability among the private sector employees in Malaysia during the pandemic Covid-19. The motivational factors were divided into work environment, extrinsic benefits, autonomy, and transparency. Based on the survey to the 52 respondents with the multiple regression analysis, it showed that all the independent variables have a significant impact to the job sustainability. The result of this study helped the managers of the private sectors identifying the contributing motivational factors to ensure the job sustainability during the pandemic. The Government can structure an initiative to help the private sector employers having a secure economic growth in the unprecedent situation. By having an enriched analysis on the motivational factors to the job sustainability especially in the private sectors, it will be contributed to the body of knowledge. It is hoped that the future study can develop the variables to be examined in the job sustainability and make a comparison between public and private sectors.